PENGARUH GREEN MARKETING TERHADAP KEPUASAN PELANGGAN: STUDI KASUS PADA TOKO RITEL MODERN LION SUPERINDO BOJONEGORO - Noor, Fauzian; Irnawati, Dwi; Kustaji, Kustaji; Agustino, Muhammad Rizqi (Jurnal Ekonomi dan Bisnis (EK dan BI), 2024)
This study aims to investigate the influence of green marketing on customer satisfaction at the Lion Superindo retail store in Bojonegoro. The research employs a quantitative approach with a cross-sectional survey design. The study population consists of Lion Superindo Bojonegoro customers, with a sample of approximately 200 respondents selected randomly.Data were collected using a specially designed questionnaire, which included questions on customers' perceptions of green marketing practices at Lion Superindo Bojonegoro and their satisfaction levels as customers. The data collection methods involved surveys conducted both online and directly in-store. The findings reveal that the green marketing variables of green product and green price do not significantly affect customer satisfaction at Lion Superindo Bojonegoro. In contrast, the variables of green place and green promotion have a significant influence on customer satisfaction in this modern retail outlet. These results highlight the importance of focusing on strategic green marketing efforts, particularly in terms of green place and promotion, to enhance customer satisfaction in the competitive retail environment.